Liver enzyme elevation and eosinophilia with atorvastatin: a case of probable DRESS without cutaneous symptoms - Arman Zereshkian; Susan Waserman (Allergy, Asthma & Clinical Immunology, 2021)
Abstract Background Drug reaction with eosinophilia and systemic symptoms (DRESS) is a potentially life-threatening hypersensitivity reaction to medication. While a relatively rare phenomenon, early identification and discontinuation of the offending agent is pivotal to patient management. To our knowledge this is the first reported case of probable atorvastatin induced DRESS syndrome without rash. Case presentation An adult female presented with 4 days of persistent fevers, abdominal and flank pain, malaise, and generalized muscle weakness without any cutaneous reaction following 20 days of therapy with atorvastatin. She was febrile (38.5 °C), at presentation with a heart rate of 72, and blood pressure of 93/51 mmHg. Her laboratory investigations at their peak demonstrated an Alkaline Phosphatase (ALP) of 792 U/L, Alanine aminotransferase (ALT) of 265 U/L, gamma glutamyl transferase (GGT) of 236 U/L, total bilirubin at 21 mg/dL, eosinophils 3100 cells/µL, leukocytes 20.2 K/µL, hemoglobin of 12.5 gm/dL. During her admission she had normal creatinine and troponin. Her serology for Hepatitis A, B and C were negative. Cytomegalovirus, Epstein-Barr viral serologies were negative. Antinuclear Antibody (ANA), rheumatoid factor, anti-neutrophil cytoplasmic antibody (ANCA), mitochondrial antibody, and smooth muscle antibody were negative. The patient was initially diagnosed as having pyelonephritis due to nonspecific bilateral flank pain but given ongoing fevers and lack of clinical and laboratory improvement with antibiotics, a diagnosis of atorvastatin induced DRESS syndrome was considered probable, and atorvastatin was discontinued. The patients’ clinical status improved gradually without any further therapy and her liver enzymes and eosinophils normalized over the course of a month. Conclusion In patients who present with systemic organ involvement and eosinophilia, even without cutaneous manifestations, clinicians should apply the RegiSCAR criteria for DRESS syndrome. This can then help guide treatment with discontinuation of offending agent, or treatment with systemic corticosteroids.